A Brief Overview of Clinico-Pathological Indicators of Breast Carcinoma - ROZINA JAFFER, MUNAZZA HASSAN, ALI AK, TAYABA JAVED (Journal of Fatima Jinnah Medical University, 2018)
Breast cancer has been rated as the 2nd most frequent type of malignancy. As regards being a cause of death, breast malignancy is ranked fifth in order. The occurrence of breast cancer in underdeveloped countries was low when compared with economically developed world. Mode of presentation varies a lot in breast carcinoma. Pain, palpable lump, knobbly bumpy breast and nipple discharge are the typical presenting modes. In 80 % of cases the most common presentation is a swelling. Pain is a nonspecific symptom regarding carcinomas. A lump is noticed when it is at least 2 cm in size. Other modes of presentation include certain changes in skin color such as redness, and orange peel like appearance (peau d orange), without the presence of lump. Sometimes a delay in diagnosis occurs as it is treated as an inflammation. Female gender is the most crucial risk factor for breast malignancy. 41 to 50 year is the peak age of breast carcinoma, occasionally at 25 years and less than 5% occur in women in age range of 70 to 80 years. Genetic makeup and women with increased estrogen levels like early menarche and late menopause also form a contributory factor. This study focuses on above mentioned clinical parameters, a few risk factors and histomorphological indicators and following formula was used {n = Z2P (1-P)} d2 Women diagnosed with invasive breast carcinoma in surgical specimens like excisional biopsies, incisional biopsies and mastectomies were included in this study and patients with recurrent breast carcinomas who have been receiving treatment line chemotherapy, radiotherapy and hormonal therapy were excluded from this study. This study showed that 55.8% cases left side was involved and in 44.1% cases right sided involvement was seen, 22.5% has breast carcinoma in their first step related while 10% has second step relative breast carcinoma and exposure of radiation was observed in 8%. The main presenting complaints were lump in breast, and skin changes (mentioned above). This study showed that lump in breast was the most common presenting complaint while nipple discharge was the second most frequent, female gender can be rendered a risk factor. The age decade which poses greatest risk was 41 to 50 years. There were cases in less than 30 and under 80 decades as well. Invasive ductal carcinoma was the most common type